BRIDGING A CHALLENGING ENGLISH TEACHING THROUGH WELL-PREPARED CLASSROOM MANAGEMENT - Mobit Mobit (JUDIKA (JURNAL PENDIDIKAN UNSIKA), 2014)
English teaching stands with some consideration. The significant components which take influences in the teaching process are lesson plan and classroom management. Lesson planning and classroom management are inseparable, because the two terms link each other. Lesson plan takes role in how to conduct the classroom in the â€œsecond-to-secondâ€ of English teaching. Teacher would be guided by the lesson plan for some supporting components. The teachersâ€™ classroom activities are influenced by the classroom management skills. classroom management comprises of how teacher should manage the studentsâ€™ motivation, how teacher should manage the classroom constraints and how teacher manage their own role in the classroom.This article discusses the previous beneficial components that succeeds the English teaching in the classroom.Key Word: Lesson Plan, Classroom Management